IMPLEMENTASI KEBIJAKAN KEPEMILIKAN DOKUMEN LINGKUNGAN - Yurianto, Rony (Jurnal Ilmu Administrasi Negara, 2016)
Policy Implementation of Environmental Document Ownership. This study aims to identify and analyze the policy implementation of SPPL ownership in Pelalawan and the factors that influence it. This study used a qualitative method with case study approach. Informants in this study was small and micro entrepreneurs, staff of Pelalawan Environment Agency and society. Data collection techniques using non-participatory observation, interview and documentation. Data analysis techniques through the procedure of presentation of data, data reduction and withdrawal / verification conclusion. The results showed that the implementation of policy ownership is still not optimal SPPL is seen from the policy objectives, the implementation process and policy results. Factors affecting policy implementation of SPPL ownership in Pelalawan is the wrong idea about the environmental impact of small and micro enterprises, lack of knowledge, budgetary constraints, socio-economic conditions of society and the ability to generate turnover is still low.